Cavitation-erosion-resistant, wear-resistant and corrosion-resistant multifunctional coating and preparation method thereof

By introducing the characteristics of reversible conversion of DA bonds into the marine coating materials and the modification of maleimide groups to reduce graphene oxide, combined with 2,5-furandimethanol-based polyurethane, reversible crosslinking is achieved, forming a multifunctional coating with cavitation resistance, wear resistance and corrosion resistance, and solving the problem of difficult recovery of thermoset elastomers.

CN119736008APending Publication Date: 2025-04-01JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411835424.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing marine coating materials are difficult to resist electrochemical corrosion, cavitation impact and fluid erosion at the same time, and the thermoset elastomers formed are difficult to recycle and reuse, resulting in waste of resources and environmental pollution.

Method used

By introducing the reversible transformation of DA bonds into the elastomer, the reduction of graphene oxide is modified by maleimide groups and introduced into 2,5-furandimethanol-based polyurethane. At the same time, the DA bond is used as the crosslinking agent to achieve reversible crosslinking, forming a multifunctional coating with recovery ability that resists cavitation, wear and corrosion resistance and corrosion resistance.

Benefits of technology

It improves the mechanical properties, hardness and molecular density of the coating, enhances its anti-cavitation corrosion, wear resistance and corrosion resistance, and at the same time realizes the recyclability of the coating, avoiding resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736008A_ABST
    Figure CN119736008A_ABST
Patent Text Reader

Abstract

According to the cavitation-erosion-resistant, wear-resistant and corrosion-resistant multifunctional coating and the preparation method thereof, the coating contains modified reduced graphene oxide, the interior of the coating is formed by crosslinking of a three-dimensional network structure, and by means of the structure, the mechanical property, hardness and molecular compactness of the coating are all improved. The wear resistance and cavitation corrosion resistance of the coating can be effectively improved by improving the mechanical property and hardness of the coating, and the corrosion medium infiltration resistance of the coating can be improved by improving the molecular compactness. And meanwhile, the modified reduced graphene oxide can generate chemical crosslinking with molecules in the coating, and various properties of the coating are further enhanced through the crosslinking mode. A cross-linking agent containing a tri-maleimide group and reduced graphene oxide modified by a maleimide group are introduced into 2, 5-furandimethanol-based polyurethane to synthesize a reversible cross-linked elastomer with a DA bond, and the reversible cross-linked elastomer is dissociated into an original unit in a special state, so that the recoverable characteristic of the elastomer is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention belongs to the technical field of marine multifunctional coatings. Background Art

[0003] Offshore engineering equipment operates in a complex and changeable marine environment, and these environmental factors impose extremely severe corrosion tests on materials. Electrochemical corrosion, cavitation corrosion and scour corrosion are the most common and most destructive forms of corrosion in the marine environment. Electrochemical corrosion is caused by electrochemical reactions of metal materials in electrolyte solutions such as seawater, which causes the metal to lose electrons and gradually dissolve. The abundant chloride ions and oxygen in seawater further accelerate this process, making improperly protected marine equipment face serious corrosion risks. Cavitation corrosion is another challenge, which often occurs in high-speed flowing liquid environments. When the liquid flow rate is high enough, cavitation will form in the low-pressure area. These cavitations will quickly collapse in the high-pressure area, releasing high-energy shock waves, causing local high-temperature and high-pressure impact on the metal surface, leading to material fatigue and erosion. Scour corrosion is the result of the combined effects of wear and chemical corrosion caused by suspended solid particles in seawater or high-speed flowing liquid on the metal surface. This form of corrosion usually causes the material surface to gradually become thinner or even perforated, seriously affecting the structural integrity and service life of the equipment.

[0004] In this context, it is crucial to develop a coating material with comprehensive protective capabilities. This coating needs to have multiple functions: first, it should be able to effectively isolate corrosive media such as seawater to prevent the occurrence of electrochemical corrosion; second, the coating must have sufficient mechanical strength and toughness to resist physical damage caused by cavitation impact and fluid scouring. In addition, the coating material must also have good adhesion and weather resistance to ensure stable performance during long-term service. In recent years, with the rapid development of nanomaterials, composite materials and smart materials, coating technology has ushered in new breakthroughs in the field of corrosion protection. By introducing nanoparticles or fiber reinforcements into the coating, its mechanical properties and corrosion resistance can be significantly improved.

[0005] By learning from various cross-linking structures in proteins, different cross-linking structures can be introduced into elastomers, and the properties and functions of elastomers can be optimized by adjusting the type, proportion and distribution of cross-linking. The presence of cross-linking structures can not only prevent interchain sliding, thereby improving the elasticity and other mechanical properties of elastomers, but also improve the compactness between molecules. In addition, previous studies by our team have also found that after adding functionalized graphene to elastomers, elastomer molecules will form cross-linked structures. This modification method can also effectively improve the mechanical properties and electrochemical corrosion resistance of elastomers. Therefore, it is expected that by adding different cross-linking structures (such as cross-linkable pairing molecules and cross-linkable pairing modified two-dimensional nanosheets) to elastomers and accurately adjusting their proportions, elastomer films that can resist three types of marine corrosion can be developed. However, thermosetting elastomers formed by existing cross-linking methods are difficult to recycle and reuse, resulting in serious waste of resources and environmental pollution. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention proposes a multifunctional coating that is cavitation-resistant, wear-resistant and corrosion-resistant. The characteristics of the reversible transformation of the DA bond are utilized, and reduced graphene oxide (M-rGO) is modified by maleimide groups and introduced into 2,5-furandimethanol-based polyurethane. At the same time, the cross-linking agent also adopts a DA bond, and reversible cross-linking is achieved through maleimide groups and 2,5-furandimethanol-based polyurethane, thereby obtaining an elastomeric coating containing a cross-linked structure and having recycling ability.

[0007] The present invention provides a method for preparing a multifunctional coating having cavitation resistance, wear resistance and corrosion resistance, and the specific steps are as follows: Step 1: Preparation of modified reduced graphene oxide: 1) Dispersing reduced graphene oxide (rGO) in an organic solvent by ultrasonic dispersion to obtain a rGO dispersion; the concentration of rGO in the rGO dispersion is 0.8-1.3 mg / mL; 2) Pour the reduced graphene oxide dispersion into a flask, add hexamethylene diisocyanate (HDI), and react for 12 h under a protective atmosphere. After the reaction is completed, obtain HDI-functionalized reduced graphene oxide by centrifugation; the mass ratio of the added HDI to rGO is 1000-10000:1; 3) dispersing the HDI functionalized reduced graphene oxide in an organic solvent by ultrasonic dispersion to obtain a HDI functionalized reduced graphene oxide dispersion; the concentration of the HDI functionalized reduced graphene oxide in the HDI functionalized reduced graphene oxide dispersion is 0.8-1.3 mg / mL; 4) pouring the HDI functionalized reduced graphene oxide dispersion obtained in step 3) into a reaction container, adding N-(2-hydroxyethyl)maleimide, reacting for 12 h under a protective atmosphere, separating the product by centrifugation after the reaction is completed, ultrasonically cleaning the separated product with butyl acetate, and finally drying it in a vacuum drying oven at 60° C. for 24 h to obtain modified reduced graphene oxide; the mass ratio of HDI functionalized reduced graphene oxide to N-(2-hydroxyethyl)maleimide is 1:1000-10000; Step 2: Prepare crosslinking agent solution: Hexamethylene diisocyanate trimer (triHDI) is mixed with an organic solvent, and N-(2-hydroxyethyl)maleimide is added to prepare a crosslinker solution; wherein the molar ratio of triHDI to N-(2-hydroxyethyl)maleimide is 1:3, and the mass ratio of the total mass of triHDI and N-(2-hydroxyethyl)maleimide to the organic solvent is 3:7; Step 3: Preparation of polyurethane prepolymer: Toluene diisocyanate (TDI) was poured into a reaction container, heated to 50°C and nitrogen was introduced, PTMG was added dropwise into the reaction container, reacted at 50°C for 30 min, then the temperature was raised to 80°C and the reaction was continued for 3 h to obtain a polyurethane prepolymer; the obtained prepolymer was bottled and sealed, cooled to room temperature and stored for later use; wherein the mass ratio of TDI to PTMG was 3:7.3; Step 4: Polyurethane prepolymer chain extension polymerization: The prepolymer and the organic solvent were poured into a beaker, the modified reduced graphene oxide was added, the mixture was ultrasonically dispersed, and then the chain extender 2,5-furan dimethanol was added; the mixture was stirred at 60°C for 24 hours, and then the mixture was cooled to room temperature to complete the prepolymer chain extension, and the coating component A was obtained; The mass ratio of the prepolymer and the chain extender 2,5-furan dimethanol to the organic solvent is 3:7; the mass ratio of the prepolymer to the chain extender 2,5-furan dimethanol is (6-7):1; the amount of modified reduced graphene oxide added is 0.25-1.5wt% of the total mass of TDI, PTMG and 2,5-furan dimethanol; Step 4: Cross-linking and curing of polyurethane prepolymer: Add the crosslinker solution obtained in step 2 to component A of the coating, stir for 1 hour, apply it to the surface of the substrate, and cure it in a vacuum oven at 80°C for 24 hours to obtain the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating; the mass ratio of the crosslinker solution to component A of the coating is (0.75-0.8):1.

[0008] Preferably, the organic solvent is N,N-dimethylformamide.

[0009] Preferably, the molecular weight of PTMG is 850.

[0010] Preferably, in step 3, the PTMG is poured into a rotary bottle of a rotary evaporator in advance, and then distilled under vacuum at 120° C. for 2 h. After cooling to 60° C., it is bottled and sealed for storage.

[0011] Preferably, the substrate is one of iron, copper, steel, magnesium, titanium, aluminum or an alloy thereof.

[0012] Beneficial effects of the present invention: The present invention proposes a multifunctional coating for cavitation resistance, wear resistance and corrosion resistance, wherein the coating contains modified reduced graphene oxide, and the interior of the coating is cross-linked and synthesized by a three-dimensional network structure, and the structure improves the mechanical properties, hardness and molecular density of the coating. The mechanical properties of the coating are improved, the improvement of hardness can effectively improve the wear resistance and cavitation resistance of the coating, and the improvement of molecular density can improve the corrosion resistance of the coating. At the same time, the modified reduced graphene oxide can also produce chemical cross-linking with the molecules inside the coating, and this cross-linking method further enhances the various properties of the coating.

[0013] The present invention introduces a cross-linking agent containing trimaleimide groups and reduced graphene oxide modified with maleimide groups into 2,5-furan dimethanol-based polyurethane to synthesize a reversible cross-linked elastomer with DA bonds. By using dynamic bonds as the cross-linking structure of the elastomer, the elastomer structure can be dissociated into original units under special conditions, thereby realizing the recyclable characteristics of the elastomer. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Mass loss after cavitation for 60 h.

[0015] Figure 2 Mass loss after 24 h of friction and wear test.

[0016] Figure 3 Comparison of low-frequency modulus values ​​after 15 days of electrochemical corrosion test. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further explained and illustrated in the form of specific embodiments below. Example

[0018] 1) Disperse 100 mg of reduced graphene oxide (rGO) in 100 ml of N,N-dimethylformamide (DMF) and disperse under ultrasonication for 1 h.

[0019] 2) Pour the reduced graphene oxide dispersion into a flask, add 1 g of hexamethylene diisocyanate (HDI), and react for 12 h under a nitrogen atmosphere. After the reaction is completed, HDI-functionalized reduced graphene oxide is obtained by centrifugation.

[0020] 3) Disperse 100 mg of HDI-functionalized reduced graphene oxide in 100 ml of N,N-dimethylformamide (DMF) and disperse by ultrasonic for 1 h.

[0021] 4) Pour the HDI functionalized reduced graphene oxide dispersion into a flask, add 1 g of N-(2-hydroxyethyl)maleimide, and react for 12 h under a nitrogen atmosphere. After the reaction is completed, separate the product by centrifugation, ultrasonically clean the separated product with butyl acetate for 3 times, and finally dry it in a vacuum drying oven at 60 ° C for 24 h to obtain modified reduced graphene oxide.

[0022] 5) Prepare a crosslinker solution by mixing 11.91 g of hexamethylene diisocyanate trimer (triHDI) with 51.12 g (53.92 ml) of DMF and adding 10 g of N-(2-hydroxyethyl)maleimide.

[0023] 6) Pour 7.3 g of polybutylene glycol (PTMG) into the rotary bottle of a rotary evaporator, and then distill it under vacuum at 120 °C for 2 h. After cooling to 60 °C, bottle it and seal it for storage.

[0024] 7) Pour 3 g of toluene diisocyanate (TDI) into a four-necked flask, heat to 50°C and pass nitrogen, pour PTMG into a constant pressure dropping funnel and drip into the four-necked flask at a rate of 4 drops per second, and react at 50°C for 30 min; then increase the temperature to 80°C and continue the reaction for 3 h to obtain a prepolymer; bottle the prepolymer and seal it, cool it to room temperature and store it.

[0025] 8) Pour 10.3 g of prepolymer and 26.6 g (28.06 ml) of DMF into a beaker, add 0.114 g of modified reduced graphene oxide, and disperse ultrasonically for 1 h; then add 1.1 g of 2,5-furan dimethanol, stir at 60 °C for 24 h, and then cool to room temperature.

[0026] 9) Add 8.9 g of crosslinker solution and stir for 1 h to obtain the coating; finally, cure in a vacuum oven at 80 °C for 24 h.

[0027] Comparative Example 1) Prepare a crosslinker solution by mixing 11.91 g of hexamethylene diisocyanate trimer (triHDI) with 51.12 g of DMF and adding 10 g of N-(2-hydroxyethyl)maleimide.

[0028] 2) Pour 7.3 g of PTMG into the rotary bottle of the rotary evaporator and then distill it under vacuum at 120 °C for 2 h. After cooling to 60 °C, bottle it and seal it for storage.

[0029] 3) Pour 3 g of TDI into a four-necked flask, heat to 50°C and pass nitrogen, pour PTMG into a constant pressure dropping funnel and drip it into the four-necked flask at a rate of 4 drops per second, and react at 50°C for 30 min; then increase the temperature to 80°C and continue the reaction for 3 h to obtain a prepolymer; bottle the prepolymer and seal it, cool it to room temperature and store it.

[0030] 4) Pour 10.3 g of the prepolymer and 26.6 g (28.06 ml) of DMF into a beaker, then add 1.1 g of 2,5-furan dimethanol, stir at 60 °C for 24 h, and then cool to room temperature.

[0031] 5) Add 8.9 g of crosslinker solution and stir for 1 h to obtain the coating; finally, cure in a vacuum oven at 80 °C for 24 h.

[0032] Effect verification like Figure 1 As shown, the ultrasonic cavitation machine was used for a 60-h test, and the mass loss of the coating sample after the test was 12.5 mg for the comparative example and 8.6 mg for the example. Compared with the comparative example, the anti-cavitation performance of the example was improved by 31.2%.

[0033] like Figure 2 As shown, a friction and wear tester was used to conduct a 24-hour test. After the test, the mass loss of the coating sample was 3.2 mg for the comparative example and 1.5 mg for the embodiment. Compared with the comparative example, the anti-friction and wear performance of the embodiment was improved by 53.1%.

[0034] like Figure 3 As shown in the figure, the low-frequency modulus value comparison after 15 days of electrochemical corrosion test, the comparative example is 6.2 ohm·cm 2 , the embodiment is 10.2 ohm·cm 2 In the low-frequency region, electrochemical impedance spectroscopy can be used to study the electrochemical reaction on the electrode surface and the physical and chemical properties of the electrode-electrolyte interface. A larger low-frequency impedance modulus value indicates that the electrolytic resistance in this region is larger, so the ion transmission rate is lower, which is not conducive to the transmission of corrosive media, and thus the anti-corrosion performance is better. Therefore, the anti-corrosion performance of the embodiment is better.

Claims

1. A method for preparing a multifunctional coating having cavitation resistance, wear resistance and corrosion resistance, characterized in that: The specific steps of this method are as follows: Step 1: Preparation of modified reduced graphene oxide: 1) Dispersing reduced graphene oxide in an organic solvent by ultrasonic dispersion to obtain a rGO dispersion; the concentration of rGO in the rGO dispersion is 0.8-1.3 mg / mL; 2) Pour the reduced graphene oxide dispersion into a flask, add hexamethylene diisocyanate, and react for 12 h under a protective atmosphere. After the reaction is completed, obtain HDI functionalized reduced graphene oxide by centrifugation; the mass ratio of the added hexamethylene diisocyanate to the reduced graphene oxide is (1000-10000):1; 3) dispersing the HDI functionalized reduced graphene oxide in an organic solvent by ultrasonic dispersion to obtain a HDI functionalized reduced graphene oxide dispersion; the concentration of the HDI functionalized reduced graphene oxide in the HDI functionalized reduced graphene oxide dispersion is 0.8-1.3 mg / mL; 4) Pour the HDI functionalized reduced graphene oxide dispersion obtained in step 3) into a reaction container, add N-(2-hydroxyethyl)maleimide, and react for 12 hours under a protective atmosphere. After the reaction is completed, separate the product by centrifugation, ultrasonically clean the separated product with butyl acetate, and finally dry it in a vacuum drying oven at 60° C. for 24 hours to obtain modified reduced graphene oxide; the mass ratio of HDI functionalized reduced graphene oxide to N-(2-hydroxyethyl)maleimide is 1:(1000-10000); Step 2: Prepare crosslinking agent solution: Mixing hexamethylene diisocyanate trimer with an organic solvent and adding N-(2-hydroxyethyl)maleimide to prepare a crosslinking agent solution; wherein the molar ratio of hexamethylene diisocyanate trimer to N-(2-hydroxyethyl)maleimide is 1:3, and the mass ratio of the total mass of hexamethylene diisocyanate trimer and N-(2-hydroxyethyl)maleimide to the organic solvent is 3:7; Step 3: Preparation of polyurethane prepolymer: Pour toluene diisocyanate into a reaction container, heat to 50°C and introduce nitrogen, add polytetrahydrofuran dropwise into the reaction container, react at 50°C for 30 min, then raise the temperature to 80°C and continue the reaction for 3 h to obtain a polyurethane prepolymer; bottle the obtained prepolymer and seal it, cool it to room temperature and store it for later use; wherein the mass ratio of toluene diisocyanate to polytetrahydrofuran is 3:7.3; Step 4: Polyurethane prepolymer chain extension polymerization: The prepolymer and the organic solvent were poured into a beaker, the modified reduced graphene oxide was added, the mixture was ultrasonically dispersed, and then the chain extender 2,5-furan dimethanol was added; the mixture was stirred at 60°C for 24 hours, and then the mixture was cooled to room temperature to complete the prepolymer chain extension, and the coating component A was obtained; The mass ratio of the prepolymer and the chain extender 2,5-furan dimethanol to the organic solvent is 3:7; the mass ratio of the prepolymer to the chain extender 2,5-furan dimethanol is (6-7):1; the amount of modified reduced graphene oxide added is 0.25-1.5wt% of the total mass of toluene diisocyanate, polytetrahydrofuran and 2,5-furan dimethanol; Step 4: Cross-linking and curing of polyurethane prepolymer: Add the crosslinker solution obtained in step 2 to component A of the coating, stir for 1 hour, apply it to the surface of the substrate, and cure it in a vacuum oven at 80°C for 24 hours to obtain the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating; the mass ratio of the crosslinker solution to component A of the coating is (0.75-0.8):

1.

2. The method for preparing the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide.

3. The method for preparing the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating according to claim 1, characterized in that: The molecular weight of polytetrahydrofuran is 850.

4. The method for preparing the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating according to claim 1, characterized in that: In step 3, the polytetrahydrofuran is poured into the rotary bottle of the rotary evaporator in advance, and then distilled under vacuum at 120° C. for 2 h. After cooling to 60° C., it is bottled and sealed for storage.

5. The method for preparing the anti-cavitation, wear-resistant and anti-corrosion multifunctional coating according to claim 1, characterized in that: The substrate is one of iron, copper, steel, magnesium, titanium, aluminum or their alloys.

6. A multifunctional coating having cavitation resistance, wear resistance and corrosion resistance prepared according to the method according to any one of claims 1 to 5.

Citation Information

Cited By

  • Graphene modified marine anticorrosive paint based on dynamic covalent bonds

    CN121673901A